Nanopharmacological Force Sensing to Reveal Allosteric Coupling in Transporter Binding Sites. (22nd December 2015) - Zhu, Rong; Sinwel, Doris; Hasenhuetl, Peter S.; Saha, Kusumika; Kumar, Vivek; Zhang, Peng; Rankl, Christian; Holy, Marion; Sucic, Sonja; Kudlacek, Oliver; Karner, Andreas; Sandtner, Walter; et al.
Abstract: Controversy regarding the number and function of ligand binding sites in neurotransmitter/sodium symporters arose from conflicting data in crystal structures and molecular pharmacology. Here, we have designed novel tools for atomic force microscopy that directly measure the interaction forces between the serotonin transporter (SERT) and the S ‐ and R ‐enantiomers of citalopram on the single molecule level. This approach is based on force spectroscopy, which allows for the extraction of dynamic information under physiological conditions thus inaccessible via X‐ray crystallography. Two distinct populations of characteristic binding strengths of citalopram to SERT were revealed in Na + ‐containing buffer. In contrast, in Li + ‐containing buffer, SERT showed only low force interactions. Conversely, the vestibular mutant SERT‐G402H merely displayed the high force population. These observations provide physical evidence for the existence of two binding sites in SERT when accessed in a physiological context. Competition experiments revealed that these two sites are allosterically coupled and exert reciprocal modulation.